Application of cofactors in the regulation of microbial metabolism: A state of the art review - Sun, Yang; Zhang, Ting; Lu, Bingqian; Li, Xiangfei; Jiang, Ling (Frontiers in Microbiology, 2023)
Cofactors are crucial chemicals that maintain cellular redox balance and drive the cell to do synthetic and catabolic reactions. They are involved in practically all enzymatic activities that occur in live cells. It has been a hot research topic in recent years to manage their concentrations and forms in microbial cells by using appropriate techniques to obtain more high-quality target products. In this review, we first summarize the physiological functions of common cofactors, and give a brief overview of common cofactors acetyl coenzyme A, NAD(P)H/NAD(P)+, and ATP/ADP; then we provide a detailed introduction of intracellular cofactor regeneration pathways, review the regulation of cofactor forms and concentrations by molecular biological means, and review the existing regulatory strategies of microbial cellular cofactors and their application progress, to maximize and rapidly direct the metabolic flux to target metabolites. Finally, we speculate on the future of cofactor engineering applications in cell factories.